1602 Switching from mycophenolate mofetil to mycophenolic acid in SLE patients: Results from the RISE registry. (14th December 2022) - Izadi, Zara; Aguirre, Alfredo; Schmajuk, Gabriela; Yazdany, Jinoos
Abstract : Background: Mycophenolate mofetil (MMF) is commonly used to treat SLE, but many patients experience gastrointestinal (GI) side effects, which are responsible for drug discontinuation in up to 30 percent of patients with SLE. 1 In the transplant literature, switching to enteric coated mycophenolic acid (Myfortic) is associated with improved gastrointestinal symptoms in up to two-thirds of patients with intolerance to MMF. 2 However, data on Myfortic use in SLE patients is limited. We aimed to investigate how often U.S. rheumatologists initiated Myfortic after MMF in people with SLE. We also examined variations in Myfortic use across U.S. rheumatology practices and analyzed patient-level factors associated with Myfortic use. Methods: Data were derived from the ACR's RISE registry. We included adults with ≥2 ICD codes for SLE ≥30 days apart and a new prescription for MMF (defined as no MMF or Myfortic use within the past 12 months). Medication starts and stops were assessed from electronic health record (EHR) medication orders and reconciled medication lists. Index date was defined as the date of MMF initiation. Patients were followed to MMF discontinuation (defined as no MMF use for a period ≥6 months) or switch, loss to follow-up (LTFU, defined as having no further visits after MMF discontinuation) or March 31, 2021, whichever occurred earliest. Documentation of common GI side effects using ICD codes during MMF use was assessed. We reported rates of discontinuation (with or without switch) and switch at 3-, 6-, and 12- months post MMF initiation. The Aalen-Johansen estimator was used to derive median time on MMF therapy, median time to switch, and median time on Myfortic therapy after switch. Among practices with ≥20 patients initiating MMF treatment, practice-level proportions of patients switching to Myfortic were reported. Fine-Gray multivariable regression analysis was used to determine factors associated with Myfortic switch. The model included sociodemographic factors (age, sex, race/ethnicity, area deprivation index [ADI], insurance type) and Charlson comorbidity index as covariates and adjusted standard errors to account for clustering at practice. Results: We included 5, 147 patients from 199 practices. Mean (SD) age was 50.8 (15.1) years and 4570 (88.8%) were female (table 1). Patients had a mean (SD) follow-up of 18.9 (22.7) months. Over the study period, a total of 3, 467 (67.4%) patients discontinued MMF (137 [4.0%] of whom switched to Myfortic), 1, 012 (19.7%) were lost to follow-up and 668 (13.0%) stayed on MMF. Any occurrence of common GI side effects during MMF use was documented in 247 (4.8%) patients (12 of whom [4.9%] switched to Myfortic). The proportion of patients switching to Myfortic varied considerably across U.S. practices (figure 1). The rate of MMF discontinuation (with or without switch) at 3-, 6-, and 12-months post MMF initiation was 16.1%, 4.5%, and 2.9%, respectively; the rate of switch from MMF to Myfortic at comparable timepoints was 0.5%, 0.2%, and 0.1%, respectively. Median time on MMF therapy was 19.0 months and median time to switch was 2.9 months. Median time on Myfortic therapy after switch was 7.5 months (36.7 months in patients with ≥2 Myfortic prescriptions ≥30 days apart). A switch was more likely in patients with higher Charlson comorbidity scores (HR: 1.14, 95%CI: 1.01-1.29) and public versus private insurance (1.71, 1.13-2.58) and less likely in patients with lower socioeconomic status, as defined by a higher ADI (0.91 per 10-units, 0.86-0.97, table 2). Including 82 practices with ≥20 patients initiating MMF. Each bar represents a practice. The remaining patients at each practice discontinued MMF (without switching to Myfortic) or were lost to follow-up. GI side effects included abdominal pain, constipation, diarrhea, flatulence, abdominal distension, decreased appetite, dyspepsia, nausea, vomiting, and the ICD10 code for GI side effects (T47.95XA). Conclusions: We found high rates of MMF discontinuation after the drug was started and that less than 5% of patients were switched to Myfortic during their course of treatment. Although treatment failure or non- GI adverse events may account for many MMF drug discontinuations, significant variations in how often rheumatologists switch to Myfortic suggests that the drug may be underutilized in some practices and in certain patient groups. References: Pisoni CN, Sanchez FJ, Karim Y, et al . Mycophenolate mofetil in systemic lupus erythematosus: efficacy and tolerability in 86 patients. The Journal of rheumatology. 2005;32 (6):1047–1052. Chan L, Mulgaonkar S, Walker R, Arns W, Ambühl P, Schiavelli R. Patient-reported gastrointestinal symptom burden and health-related quality of life following conversion from mycophenolate mofetil to enteric-coated mycophenolate sodium. Transplantation. 2006;81 (9):1290–1297.